PENGARUH RASIO-RASIO KEUANGAN DAN UKURAN PERUSAHAAN PADA RETURN SAHAM - Raningsih, Ni Kadek; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2015)
Return is the result obtained from an investment. Stock returns are influenced by various factors such as the ratio of profitability, leverage, liquidity, activity, and firm size. The purpose of this study was to determine the effect of the ratio of profitability, leverage, liquidity, activity, and firm size on stock returns. Sampling method in this research was purposive sampling and acquired 32 observational data as the sample. The data used in this research was secondary data. The data analysis technique used was multiple linear regression using SPSS 17.0. The results showed that profitability and leverage ratios positive effect on stock returns, liquidity ratios negative effect on stock returns, and the ratio of the activity and firm size has no effect on stock returns.
Keywords: Activity Ratio, Leverage, Liquidity, Profitability, Stock Returns, Firm Size